A Semi-natural Approach for Studying Seasonal Diapause in Drosophila melanogaster Reveals Robust Photoperiodicity. Issue 2 (April 2018) - Nagy, Dóra; Andreatta, Gabriele; Bastianello, Stefano; Martín Anduaga, Ane; Mazzotta, Gabriella; Kyriacou, Charalambos P.; Costa, Rodolfo
The fruit fly Drosophila melanogaster survives thermally stressful conditions in a state of reproductive dormancy (diapause), manifested by reduced metabolic activity and arrested ovarian development in females. Unlike insects that rely primarily on photoperiodic stimuli to initiate the diapause program, in this species dormancy is regulated by low temperature and enhanced by shorter photoperiods. Overwintering phenotypes are usually studied under simple laboratory conditions, where animals are exposed to rectangular light-dark (LD) cycles at a constant temperature. We sought to adopt more realistic diapause protocols by generating LD profiles that better mimic outdoor conditions. Experimental flies were subjected to semi-natural late autumn and summer days, while control females received the same amounts of light but in rectangular LD cycles (LD 8:16 and LD 15:9, respectively). We observed that semi-natural autumnal days induced a higher proportion of females to enter dormancy, while females in semi-natural summer days showed reduced diapause compared with their corresponding rectangular controls, generating an impressive photoperiodic response. In contrast, under rectangular light regimes, the diapause of Drosophila field lines exhibited minimal photoperiodicity. Our semi-natural method reveals that D. melanogaster diapause is considerably more photoperiodic than previously believed and suggests that this seasonal response is best studied under simulated natural lighting conditions.